An Overview of Solar Orbiter Observations of Interplanetary Shocks in Solar Cycle 25 - Domenico Trotta; Andrew Dimmock; Heli Hietala; Xochitl Blanco-Cano; Timothy S. Horbury; Rami Vainio; Nina Dresing; Immanuel Christopher Jebaraj; Francisco Espinosa Lara; Raúl Gómez-Herrero; Javier Rodriguez-Pacheco; Yulia Kartavykh; et al. (The Astrophysical Journal Supplement Series)
Interplanetary (IP) shocks are fundamental constituents of the heliosphere, where they form as a result of solar activity. We use previously unavailable measurements of IP shocks in the inner heliosphere provided by Solar Orbiter, and present a survey of the first 100 shocks observed in situ at different heliocentric distances during the rising phase of solar cycle 25. The fundamental shock parameters (shock normals, shock normal angles, shock speeds, compression ratios, Mach numbers) have been estimated and studied as a function of heliocentric distance, revealing a rich scenario of configurations. Comparison with large surveys of shocks at 1 au shows that shocks in the quasi-parallel regime and with high speed are more commonly observed in the inner heliosphere. The wave environment of the shocks has also been addressed, with about 50% of the events exhibiting clear shock-induced upstream fluctuations. We characterize energetic particle responses to the passage of IP shocks at different energies, often revealing complex features arising from the interaction between IP shocks and preexisting fluctuations, including solar wind structures being processed upon shock crossing. Finally, we give details and guidance on the access use of the present survey, available on the EU-project “Solar Energetic Particle Analysis Platform for the Inner Heliosphere” website. The algorithm used to identify shocks in large data sets, now publicly available, is also described.